HUKUM PERJANJIAN DAN PENYELENGGARAAN JASA KONSTRUKSI - Miftahol Fajar Sodik; Imam Rofiqi; Darma Jasuli (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2021)
Construction services have the aim of realizing a just and prosperous society, this is based on Law number 2 of 2017 concerning construction services which replaces Law No. 18 of 1999, improvement of the rules was carried out due to lack of legal certainty in the content of law number 18 of 1999 concerning construction services relating to the implementation and agreement Construction service activities act as a supporter of national economic development and are one of the productivity factors to mobilize growth in each region at the district or city / professional level. Civil service construction services emphasizing implementation agreements are based on law number 2 of 2017 concerning construction services so that all rights and obligations can be realized by referring to benefits, safety, equality and fairness. The construction of construction must be carried out by looking at the provisions stipulated in articles 2, 38 and other sub-articles that are interrelated because construction services are activities of instruction that have an impact on the environment and sustainable development. The construction agreement must be made on the document that contains the formulation of the work, a clear and detailed description of the scope of work, the value of the work, unit prices, lump sums, and time limits for implementation. Equitable Rights and Obligations, containing the right of the Service User to obtain the results of Construction Services and their obligations to fulfill the agreed conditions, as well as the right of the Service Provider to obtain information and compensation for services and obligations to carry out Construction Services services. This means that the document of the agreement must contain everything that was promised in the implementation of construction services so that the consensus agreement on the agreement is a legal engagement (the law) of both parties which consequently with violation of rights and obligations between users and providers of construction services. Arrangements and construction agreements must be carried out in an environmentally sound manner and guarantee public order and legal certainty, meaning that construction construction must have a goal of realizing a just and prosperous society, and to function as a supporter of social and economic social infrastructure.